Determination of Salicylic Acid in Anti Acne Cream which Circulated Around Bandung City Using Ultra Violet Spectrophotometry Method - Ginayanti Hadisoebroto; Senadi Budiman (Jurnal Kartika Kimia, 2019)
Salicylic acid is an anti-acne as well as keratolytic which is commonly given topically. The purpose of this study was to determine the levels of salicylic acid in anti-acne creams circulating in traditional markets, supermarkets, and skin care in Bandung, and to compare the levels of salicylic acid in samples with the maximum salicylic acid content limit determined by the Center for Drug and Food Control (BPOM). Qualitative analysis using the thin layer chromatography (TLC) method with the toluene mobile phase: acetic acid (4: 1) and color test using FeCl3 reagent. While the quantitative analysis of salicylic acid in anti-acne cream using ethanol solvent and measured by a UV spectrophotometer. Method validation to prove that the method used has reached the requirement. Salicylic acid levels in sample G were 2.33%, C 1.54%, B 0.71%, R 0.85%, and I 0.82%. Samples C, B, R and standard sample set by BPOM which is no more than 2%. Sample G does not unqualified because the level is more than 2%.